China’s music industry unplugged: Business models, copyright and social entrepreneurship in the online platform economy - Chen, Z.T. (2019)
This research project focuses on the music industry in China, to discuss proper business models through which revenue can be generated and maintained with a shifting demographic audience base, where an increasing number of people are consuming music online and in the cloud. The first part of the thesis provides a socio-legal analysis of the development of Chinese copyright law with a focus on the music industry. I take a historical approach and provide much neglected evidence of the autonomous development of Chinese copyright law. I aim to address the paradox between the weak copyright regime in China and its recent seemingly positive development in the music industry, particularly in the online digital sector. This part will lay the foundation for the discussion of policy implications and specific recommendations facing the third amendment of Chinese copyright law. It also generates relevant themes which will guide the analysis in Part II of this thesis in addressing the research questions about potential business models, strategies and tactics, with an aim to get artists and creators fairly compensated. In Part II, I will first investigate the traditional model, then focus on recent changes in the music industry which might bring a paradigm shift in the future, namely the renegade model and the platform ecosystem model in the digital platform economy. I argue that these models are not substitutes for each other; rather they will co-exist and evolve within the creative industry ecology. Inspired by social entrepreneurship theories, policy makers, practitioners and businesses can be selective and choose their own models based on their respective visions, recourses, and expertise to leverage their own strength. The dual approach of copyright protection (litigation strategy) and business model innovation reflects the complexity of the music industries, where maintaining fair compensation for artists by copyright law and adjusting business models in light of changing technologies and social network markets become two competitive and complementary narratives. Policy implications and recommendations, with regard to specific provisions of copyright law in China, will be articulated in the conclusion chapter.